(untitled) (Research, Society and Development, 2020)
The purpose of this research was to describe the professional profile of those affected by the fall of the Fundão dam, which occurred in 2015, in the city of Mariana (Minas Gerais - Brazil). This is justified by the loss of work on the part of those affected and the need for professional profile adequacy, considering the conditions of the market in the Mariana-MG region. This first academic effort to understand the professional profile of those affected by the fall of the Fundão dam contributes to the design of public policies, research projects and university extension and/or proposals for partner actions, which aim to seek to rebuild the means of work of those affected or the training of them for the labor market of Mariana and region. A conclusive descriptive qualitative research was conducted, with the application of 62 questionnaires with those affected. The data were analyzed using descriptive statistics techniques and content analysis. The profissiographic profile of those affected by the colapse of the Fundão dam presents important data on the difficulty of professional replacement of this public in the Mariana-MG region. Much is due to the different work logic they had in their localities of origin. Prospects of the future, however, are glimpsed by those affected as a way of rebuilding their lives in the field of work.